Current Problems of Quality of Education in Armenia - Galstyan, Marina (Journal of Sociology: Bulletin of Yerevan University, 2021)
Education policy makers are constantly faced with the problem of "ambiguous interpretation" of the concept of "quality of education". Different social groups give different interpretations of the quality of education, creating their own discourse on the quality of education. Mutual agreement between these groups is possible only if they mutually understand the discourse created by them. The article addresses the discourse on "quality of education" using complex methodology. Education policy makers circulate the following comment on the quality of education: correspondence with state educational standards. The management staff of private universities emphasizes the existence of a state accreditation as a guarantee of the quality of education provided, in the case of state universities, a state diploma. Students as a social group interpret the quality of education as compliance with the requirements of the labor market, and employers as work effectiveness. A sociological analysis of the situation provides an opportunity to identify the nature of the discourse fields created on the quality of education, their peculiarities and the possibilities of harmonization between them.
Keywords: quality of professional education; educational policy; educational reforms; discourse analysis; education in Armenia